HUBUNGAN KEMIRINGAN LERENG DAN PERSENTASE BATUAN PERMUKAAN TERHADAP LONGSOR BERDASARKAN HASIL SIMULASI - Rinovian Tri Saputra; Sri Rahayu Utami; Christanti Agustina (Departemen Tanah, Fakultas Pertanian, Universitas Brawijaya, 2022)
Landslide is the process of moving slope-forming material that moves out of the slope. Landslides cause adverse impacts, such as damage to residences, public facilities, death tolls, and damage to agricultural land. Factors for landslides are influenced by disturbing slope stability due to steep slopes, high rainfall intensity, and movement of soil, rock, or a mixture of both. The research was conducted at Agro Techno Park of Brawijaya University (silt loam texture soil) and the experimental field of Faculty of Agriculture Brawijaya University (clay texture soil). The landslide simulation tool used acrylic (100 cm x 50 cm x 75 cm), with an aluminum plate as a base for adjusting the slope. Artificial rain was set to be stable at an intensity of 70 mm hour-1. This study used a combination of three factors, namely soil texture (C: silt loam and J: clay); slope (L1: 40° and L2: 50°); and surface rock (B1: 25% and B2: 50%), so that there were eight treatments with ten repetitions. The landslide duration and volume were measured. The data obtained were then statistically analyzed through the normality test and the unpaired t-test. The results show that increasing slope gradient from 40° to 50° on silty loam texture with similar rock content at the soil surface resulted in 6 times faster and two times larger landslide volume. At a very steep slope, the effect of soil texture and % rocks at the surface would be smaller on landslide duration but became more significant on landslide volume. Generally, the landslide factors can be ranked from the most significant effect as follows: slope gradient, soil texture, and rocks coverage at the surface.